Training in nuclear forensic science: the Australian experience supporting the development of regional capabilities. (29th July 2019) - Toole, K.; Bull, T.; Keegan, E.; Goralewski, J.; Griffiths, G.; Hill, D.; Lee, S.; Smith, K. L.; Young, E.; Reinhard, M.
ABSTRACT: ANSTO is recognized internationally for its capabilities in nuclear forensic science, with nearly two decades of operational and research experience. As such, ANSTO is frequently requested to provide training to nations in the South-East Asia region who are seeking to develop and advance nuclear forensic capabilities. This paper will provide three examples of nuclear forensic training provided by ANSTO in South-East Asia. These case studies are utilized to explore the benefits and limitations of various modalities of nuclear forensic training. Some of the unique challenges of providing training in CBRN (chemical, biological, radioactive and nuclear) science are elucidated. Best practices for the implementation of nuclear forensic training are described.